La decelerazione pandemica come apertura di potenziali di trasformazione sociale. Alcuni percorsi di teoria critica - Fazio, Giorgio (SocietàMutamentoPolitica, 2023)
The global health crisis related to the spread of the Covid-19 pandemic has restored unexpected relevance to certain theoretical schemes that are part of the conceptual heritage of the Frankfurt critical theory. In particular, a new actuality seemed to regain the nexus between crisis, critique and emancipation, thematized in this tradition of critical thinking. Building on this premise, the article discusses a series of interventions on the pandemic crisis by exponents of contemporary critical theory, particularly those of Axel Honneth, Nancy Fraser, and Hartmut Rosa. In particular, the interventions of the latter provide a starting point for reasoning about the conceptual resources offered by Rosa’s critical acceleration theory for thinking critically and politically about the pandemic event. The article highlights the political deficits of Rosa’s resonance theory.